Artificial neural network for precipitation and water level predictions of Bedup River - Bustami, R.; Bessaih, N.; Bong, C.; Suhaili, S. (Universiti Malaysia Sarawak, UNIMAS, 2007)
This study aims to improve water level prediction at Bedup River with estimations made to absent precipitation data, both using Artificial Neural network (ANN). Studies to predict water level in the state of Sarawak, Malaysia have been actively carried out.